Influence of claystone deterioration on shear strength of backfill - Pisut Rodvinij (2018)
© Int. J. of GEOMATE. Claystone in Mae Moh mine after excavation has been used as a backfill material to counterweight instability slope. However, claystone deteriorates when it has been exposed to wet-dry process in the natural condition. The investigation on the properties of claystone under natural condition and control condition can clarify the deterioration effect due to wet-dry process. Deterioration can be defined as the alteration process on size distribution and strength of claystone. Sieve analysis test and unconfined compression test were conducted on claystone samples to investigate the deterioration effect on size distribution and strength of claystone. Claystone exposed to natural condition having a decrease of an average particle size (D50) to be approximately 50 mm in 12 weeks and unconfined compressive strength of claystone was decreased 45% in 3 weeks. In contrast, claystone under control condition gave the same size distribution and unconfined compressive strength slightly decreased. Thus, the result demonstrated wet-dry process in natural condition was the main cause of claystone deterioration. The decrease on size distribution of claystone due to deterioration can be the cause of reduced on backfill shear strength. In order to clarify this assumption, direct shear test was conducted on 3 different particle sizes of claystone to simulate the effect of size reduction on shear strength of backfill. The experimental results demonstrated shear strength of the larger particle size samples was higher than the smaller especially under high normal stress. In conclusion, the deterioration of claystone significantly affects on shear strength of backfill.